1969
DOI: 10.1111/j.1365-2389.1969.tb01555.x
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Low Levels of Copper by Humic Acid

Abstract: Summary Most of the Cu previously added to humic acid derived from a sedge fen peat was easily removed by washing with acid, but the strength of binding increased as the Cu content decreased. The capacity to retain firmly bound Cu was reduced to about half by treating the humic acid to block either carboxyl or hydroxyl groups alone or to block both groups together. The retaining sites blocked therefore probably involve both carboxyl and hydroxyl groups acting together, but alternatively could be groups such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

1976
1976
2007
2007

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 11 publications
2
9
0
1
Order By: Relevance
“…The observation that the strength of binding of Cu by humic acids decreases with an increase in the amount of Cu applied (43,55,56) is in agreement with other observations suggesting that Cu, when present in low amounts in peat soils, is so tightly complexed that it cannot be taken up by crop plants. Ennis and Brogan (49) prepared a Cu·humic acid complex by saturation with CuS0 4 and found that the Cu became increasingly unavailable to oat plants as more and more of the Cu was removed by chemical extraction (increasing concentrations of HCI were used).…”
Section: Aa------decrease In Exchange-acid1ty--------------~5oosupporting
confidence: 87%
“…The observation that the strength of binding of Cu by humic acids decreases with an increase in the amount of Cu applied (43,55,56) is in agreement with other observations suggesting that Cu, when present in low amounts in peat soils, is so tightly complexed that it cannot be taken up by crop plants. Ennis and Brogan (49) prepared a Cu·humic acid complex by saturation with CuS0 4 and found that the Cu became increasingly unavailable to oat plants as more and more of the Cu was removed by chemical extraction (increasing concentrations of HCI were used).…”
Section: Aa------decrease In Exchange-acid1ty--------------~5oosupporting
confidence: 87%
“…This may be partly because such soils contain relatively little copper, but also because, as has long been suspected, the copper present is complexed by organic matter m a form unavailable to plants. Ennis and Brogan (1961) and Ennis (1962a) saturated humic acid and peat with copper salts, washed out excess cop er with acid, and showed in pot experiments that the studies on such complexes have been made (Ennis, 1962b;Mortensen, 1963;Davies et al, 1969). These have shown that most of the copper availability of t R e residual copper to oats was very low.…”
Section: Discussionmentioning
confidence: 99%
“…Many chemical complexes, which involve phenolic, hydroxyl, and/or carboxyl groups, are com aratively weak and their formation may be blocked by methylation. &e amounts of copper strongly held by organic matter are only partially reduced by prior methylation (Ennis, 1962b;Davies et al, 1969) which suggests that other groups are involved in the most stable complexes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the dialysability of the metals gelow pH 6, and their ready exchange on clay in the same pH range, suggests that they should be available under these more acid conditions, whereas the unavailability of Cu in acid eat soils is well known. Davies et al (1969) the Cu content decreased, and Ng et al (I 974) found that the proportion of the added Cu that was extracted from peat at pH 3 decreased with decreasing total Cu contents. It is possible that the relatively large metal : organic matter ratios used in our study may have distorted the association that is of considerable sta b ility under weakly acid and organic matter had no effect on the exchange o f t R e metal on soil clay maximum removal o F Cu occurred at pH 4.…”
Section: Discussionmentioning
confidence: 95%